Second-generation bioethanol of hydrothermally pretreated stover biomass from maize genotypes. (July 2016) - Barros-Rios, Jaime; Romani, Aloia; Peleteiro, Susana; Garrote, Gil; Ordas, Bernardo
Abstract: Twelve maize genotypes, were agronomically evaluated and their stover hydrothermally pretreated in a temperature range of 210–225 °C to assess the effects of genotype and pretreatment severity on stover recalcitrance toward bioethanol conversion. Maize genotypes exhibited significant variation for biomass yield and all agronomic evaluated, while among all cell wall constituents measured in the unpretreated stover, only ash content showed differences among genotypes. The pretreatment severities assayed impacted most stover compositional traits, and the glucose recovered after enzymatic hydrolysis displayed a similar profile among genotypes with similar genetic background. Harsher pretreatment conditions maximized the potential cellulosic bioethanol production (208–239 L/t), while the mildest maximized the bioethanol from the hemicellulosic hydrolysates (137–175 L/t). Consequently, when both pentose and hexose sugars were considered, the total potential bioethanol produced at the lowest and highest pretreatment temperatures was similar in all genotypes (292–358 L/t), indicating that the lowest temperature (210 °C) was the optimal among all assayed. Importantly, the ranking of genotypes for bioethanol yield (L/ha) closely resembled the ranking for stover yield (t/ha), indicating that breeding for biomass yield would increase the bioethanol production per hectare regardless of the manufacturing process. Similarly, the genetic regulation of corn stover moisture is possible and relevant for efficient energy production as biomass moisture has a potential impact on stover transportation, storage and processing requirements. Overall, these results indicate that local landrace populations are important genetic resources to improve cultivated crops, and that simultaneous breeding for production of grain and stover bioethanol is possible in corn. Highlights: Conversion qualities were similar among genotypes with similar genetic background. The lowest pretreatment temperature was the optimal among all assayed. Stover biomass yield is a relevant trait for developing new maize energy ideotypes Stover moisture can be genetically reduced to facilitate its store and transport. Local landrace populations are valuable genetic resources for crop improvement.